2020
DOI: 10.5219/1310
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of processed cheese spread after freeze-dried and oven-dried grape skin powder addition

Abstract: Processed cheese spread (PCS) is a popular product with high nutritional value and containing protein, fat and minerals. Grape skin is waste from winery processing plants that still has phenolic substances with significant antioxidant activity that could be used for valorisation of processed cheese and increasing the content of nutrients, phenolics and overall antioxidant properties. Both oven-dried (OD) and freeze-dried (FD) grape skin (GS) powder was characterised by the principal ingredients, the content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The levels of fat in control and experimental cheeses were in the range 44.52–46.31% DM and 39.71–41.83% DM, respectively, while protein content ranged between 43.55% and 46.62% DM in control cheeses and between 47.50% and 50.19% DM in experimental cheeses. A similar behavior was also observed by Marchiani et al [ 14 ] and Frühbauerová et al [ 45 ] in GPP added cow’s cheeses. Moreover, the lower fat content of GPP added cheeses explains their higher hardness, evaluated as resistance to compression, than that registered in control cheeses.…”
Section: Resultssupporting
confidence: 87%
“…The levels of fat in control and experimental cheeses were in the range 44.52–46.31% DM and 39.71–41.83% DM, respectively, while protein content ranged between 43.55% and 46.62% DM in control cheeses and between 47.50% and 50.19% DM in experimental cheeses. A similar behavior was also observed by Marchiani et al [ 14 ] and Frühbauerová et al [ 45 ] in GPP added cow’s cheeses. Moreover, the lower fat content of GPP added cheeses explains their higher hardness, evaluated as resistance to compression, than that registered in control cheeses.…”
Section: Resultssupporting
confidence: 87%
“…Films containing oven‐dried LRRP could inhibit more microorganisms of RFMSs than those containing freeze‐dried LRRP, which might be due to the higher phenolic compounds in the oven‐dried LRRP. However, Frühbauerová et al (2020) have reported that oven‐dried grape skin powder had lower antioxidant activities than freeze‐dried grape skin powder due to higher phenolic compounds in freeze‐dried grape skin powder compared to those in oven‐dried grape skin powder. Thus, the differences between these studies were largely due to the fact that more phenolic compounds might inhibit more microbial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, effects of adding powders to processed cheese spreads at the rate of 1% and 2% (w/w) levels were observed. (Frühbauerová et al, 2018) [21] .…”
Section: Dairy Spreads 21 Cheese Spreadmentioning
confidence: 99%